Impact of endoscopic ultrasound on diagnosis and management of presumed mucinous neoplasms when done for pancreatic cyst morphology change on non-invasive surveillance imaging - Madhani, Kamraan; Yousaf, Muhammad; Aamar, Ali; Ooka, Kohtaro; Muniraj, Thiruvengadam; Aslanian, Harry; Salem, Ronald; Farrell, James J (Endoscopy International Open, 2019)
Background and study aims Guidelines for management of presumed neoplastic pancreatic cysts have encouraged noninvasive imaging for low-risk surveillance, while reserving endoscopic ultrasound for worrisome features including morphologic change. We aim to study the impact of endoscopic ultrasound on diagnosis and management compared with non-invasive imaging.Patients and methods A single-institution pancreatic cyst database was retrospectively queried for patients who underwent endoscopic ultrasound for the indication of change in cyst morphology. Diagnoses were classified as presumed mucinous neoplasm with or without worrisome features or high-risk stigmata and non-mucinous lesions. Management decisions were defined a priori as surgical evaluation for patients with high-risk stigmata, positive cytology or mural nodule, or continued surveillance for all others. Results Between January 2013 and October 2016, 709 pancreas cyst endoscopic ultrasounds were performed of which 89 were for cyst morphology change seen on noninvasive imaging including 10 presumed pseudocysts, nine presumed serous cystadenomas, and 70 presumed mucinous cystic neoplasms. Cyst morphologic changes included increase in caliber of the main pancreatic duct (7 cases), increase in cyst size (68 cases), cyst ≥ 30 mm (10 cases), and presence of a solid nodule (1 case). Median cyst size increase was 5 mm with interquartile range of 4 mm over 2.1 ± 1.9 years. Endoscopic ultrasound done for morphologic change resulted in a change in diagnosis and management in 16 % and 13 % of cases, respectively. Conclusion Endoscopic ultrasound has a modest but clinically significant role in impacting diagnosis and management for presumed mucinous cystic neoplasms when performed for the indication of cyst morphology change.